Perceptions of Shared Decision Making and Decision Aids Among Rural Primary Care Clinicians - King, Valerie J. (2012)
BACKGROUND: Shared Decision Making (SDM) and Decision Aids (DAs) increase patients’ involvement in healthcare decisions and enhance satisfaction with their choices. Studies of SDM and DAs have primarily occurred in academic centers and large health systems, but most primary care is delivered in smaller practices and over 20% of Americans live in rural areas where poverty, disease prevalence and limited access to care may increase the need for SDM and DAs. OBJECTIVE: To explore perceptions and practices of rural primary care clinicians regarding SDM and DAs. DESIGN: Cross sectional survey. SETTING AND PARTICIPANTS: Primary care clinicians affiliated with the Oregon Rural Practice-based Research Network (ORPRN). RESULTS: Surveys were returned by 181 of 231 eligible participants (78%), 174 could be analyzed. Two-thirds of participants were physicians, 84% practiced family medicine, and 55% were male. Sixty five percent of respondents were unfamiliar with the term “SDM”, but following definition, 97% reported they found the approach useful for conditions with multiple treatment options. Over 90% of clinicians perceived helping patients make decisions regarding chronic pain and health behavior change as moderate/hard in difficulty. Although 69% of respondents preferred that patients play an equal role in making decisions, they estimate this happens only 35% of the time. Time was reported as the largest barrier to engaging in SDM (63%). Respondents were receptive to using DAs to facilitate SDM in printed (95%) or web-based formats (72%) and topic preference varied by clinician specialty and decision difficulty. CONCLUSIONS: Rural clinicians recognized the value of SDM and were receptive to using DAs in multiple formats. Integration of DAs to facilitate SDM in routine patient care may require addressing practice operation and reimbursement.